2014
DOI: 10.1515/plass-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Among Ethiopian Coffee (Coffea Arabica L.) Collections Available In Indian Gene Bank Using Sequence Related Amplified Polymorphism Markers

Abstract: The South-Western highlands of Ethiopia are considered to be the centre of origin and diversity of the arabica coffee, Coffea arabica. More than 80 accessions of arabica coffee collected from Ethiopia are available in Indian gene bank. However, the genetic diversity of these accessions is not studied in detail. In the present study, genetic diversity analysis of 48 accessions collected from eight provinces of Ethiopia was carried out using Sequence-related amplified Polymorphism (SRAP) marker. Among the thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
9
1
Order By: Relevance
“…The PCR amplification was obtained with 14 combinations of 12 primers (5 forward and 7 reverse) (Table 3) which were selected from Mishra et al (2014) to show the highest percentages of polymorphism. The PCR amplification was carried out in 10 μL containing 60 ng DNA, 3 mM each primer, 2.5 mM MgCl2, 0.2 mM dNTPs, 1 U Taq DNA polymerase and 1X buffer solution.…”
Section: Srap Markersmentioning
confidence: 99%
See 3 more Smart Citations
“…The PCR amplification was obtained with 14 combinations of 12 primers (5 forward and 7 reverse) (Table 3) which were selected from Mishra et al (2014) to show the highest percentages of polymorphism. The PCR amplification was carried out in 10 μL containing 60 ng DNA, 3 mM each primer, 2.5 mM MgCl2, 0.2 mM dNTPs, 1 U Taq DNA polymerase and 1X buffer solution.…”
Section: Srap Markersmentioning
confidence: 99%
“…The PCR amplification was carried out in 10 μL containing 60 ng DNA, 3 mM each primer, 2.5 mM MgCl2, 0.2 mM dNTPs, 1 U Taq DNA polymerase and 1X buffer solution. The amplification profile was set according to Mishra et al (2014). The amplification products were separated by electrophoresis on 2.5% agarose gels and visualized under UV light.…”
Section: Srap Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNA profiling technique using Random amplified polymorphic DNA (RAPD) and inter-simple sequence repeats (ISSR), is extensively used in plants for the study of biodiversity, gene identification, and identifying markers linked with traits of interest. Plant genetic stability study using molecular markers in medicinal plants like Withania somnifera and Capparis deciduas (Tyagi et al, 2010) and other plants like coffee species (Mishra et al, 2014), artichoke (Sharaf-Eldin et al, 2015), bamboo (Desai et al, 2015), rye grass (Ghariani et al, 2015), and lemongrass (Bishoyi et al, 2016) has been reported.…”
Section: Introductionmentioning
confidence: 99%